The Association of moisture intake and constipation among us adults: evidence from NHANES 2005–2010 - Deng-Chao Wang; Xue-Feng Peng; Wen-Xing Chen; Miao Yu (BMC Public Health)
Abstract Background Constipation is a common gastrointestinal disorder that affects the quality of life of millions of adults worldwide. Dietary moisture intake is considered to have a significant impact on intestinal health, yet its specific role in constipation has not been thoroughly investigated in large-scale population studies. This study aims to explore the correlation between adult dietary moisture intake and constipation by analyzing the NHANES database, filling a knowledge gap in the literature. Methods Data from NHANES participants aged 20 years and older from 2005 to 2010 were analyzed. Moisture intake was assessed using dietary recall data, which included moisture from all food and beverages consumed. A weighted logistic regression model was used to assess the relationship between moisture intake and the risk of constipation, calculating the odds ratios (ORs) and their 95% confidence intervals (CIs), while controlling for potential confounders. Additionally, restricted cubic splines (RCS) were applied to further explore potential non-linear patterns in the relationship between moisture intake and constipation, along with subgroup analysis. Results The study included 14,492 participants, of whom 1,514 reported constipation issues. After adequately adjusting for confounders, a significant negative correlation was observed between moisture intake and constipation risk (OR 0.81; 95% CI: 0.74–0.89). Quartile analysis of moisture intake demonstrated that, compared to the first quartile Q1 (0.06 to 1.90 kg), the constipation risk for the second quartile Q2 (1.91 to 2.53 kg), third quartile Q3 (2.54 to 3.36 kg), and fourth quartile Q4 (3.37 to 16.97 kg) were OR 0.80 (95% CI: 0.64–0.72), OR 0.57 (95% CI: 0.45–0.72), and OR 0.54 (95% CI: 0.44–0.67) respectively, with a trend test P-value ofless than 0.001. RCS regression revealed a significant non-linear negative relationship between moisture intake and constipation prevalence (P < 0.001). Depression may modulate the relationship between moisture and constipation (interaction effect P = 0.014). Conclusion The findings of this study indicate that appropriate dietary moisture intake is significantly associated with a lower risk of constipation, demonstrating a dose-response relationship. This emphasizes the importance of considering adequate moisture intake in the prevention and management of constipation. Future studies should adopt a prospective design to further verify the causal relationship between dietary moisture intake and constipation progression.